Facile fabrication of polypyrrole/NiOx core‐shell nanocomposites for hydrogen production from wastewater - Atta, A.; Negm, H.; Abdeltwab, E.; Rabia, Mohamed; Abdelhamied, M. M. (Polymers for advanced technologies, 2023)
This work highlights testing the polymer nanocomposite for hydrogen gas production from wastewater (sewage water). The in‐situ polymerization technique is used to prepare polypyrrole (PPy) and PPy/NiOx nanocomposite films on a glass substrate. The film's ability to generate hydrogen from sewage water is then evaluated. The XRD and XPS confirmed the formation of two types of NiOX: NiO and Ni2O3. The optical property of the composite is greater than the polymer under the insertion of NiOx as a core for the polymer coating shell, in which the band gap values are 2.25 and 1.81 eV, respectively. The TEM confirmed the PPy/NiOx core‐shell formation, in which the polymer shell (20 nm) coated the NiOX core (170 nm). The electrochemical testing for H2 gas production is carried out through a three‐electrode cell. The effect of light on/off, wavelengths, and temperature on the H2 production is applied. Under off/on light, the produced current density (Jph) value is enhanced from 5 to 16 μA, respectively. The effect of monochromatic light: 440, 540, and 730 nm are tested, and the produced Jph values are −1.28, −1.16, and −1.14 μA cm−2, respectively. In which, the decreasing Jph value with increasing of the monochromatic light confirmed the behavior of the photoelectrode under different optical regions. The Jph values increase from −1.6 to −5.8 μA cm−2 with a rise in temperature from 30 to 55°C. Moreover, enthalpy (ΔH*), activation energy (Ea), and entropy (ΔS*) of thermodynamic processes are determined using the photoelectrode response at different temperatures.